Association of Serum Albumin Level in Predicting of Preeclampsia among Pregnant Women in Dhaka City of Bangladesh - Begum, Taslima; Habib, Md Anwar; Chaudhury, Shipra; Akter, Hasina; Firdousi, Tahmida; Hafez, Fahmida; Mohammad, Nur; Amin, ABM Ruhul (Journal of Current and Advance Medical Research, 2019)
Background: Serum albumin level is very important during the pregnancy for the good outcome of delivery. Objective: The purpose of the present study was to see the association of serum albumin level in predicting of preeclampsia among the pregnant women. Methodology: This descriptive cohort study was conducted in the OPD of the Department of Obstetrics and Gynaecology at Rajshahi Medical College Hospital, Rajshahi, Bangladesh from January 2013 to December 2014 for a period of two (2) years. This study was carried on pregnant woman attending in outdoor department of Gynaecology, Rajshahi Medical College Hospital, Rajshahi, Bangladesh before 20 weeks of pregnancy who were healthy normotensive primigravidae with singleton pregnancy. Healthy normotensive primigravidae with singleton pregnancy were enrolled in this study before 20th weeks and were followed up after 28th weeks of pregnancy. The data of serum albumin in gm/dL before 20th weeks and after 28th weeks of pregnancy were collected. Result: A total number of 75 pregnant women were finally included in this study. PE was identified in 12(16%) women out of 75 patients on the basis of one or more following parameters. Mean serum albumin in 1st visit was 3.84±0.41 gm/dL. No association was found between development of preeclampsia and levels of serum albumin in early trimester of pregnancy (p=0.960). Conclusion: In conclusion serum albumin level is not a predictor of development of preeclampsia among the pregnant women in early stage. Journal of Current and Advance Medical Research 2019;6(2):83-86